Exploration, phenolic content determination, and antioxidant activity of dominant pteridophytes in Gunung Malang Village, Mount Halimun Salak National Park, Indonesia - RINDITA RINDITA; vivi anggia; EKA RAHMAESA; RETNA KUSUMA DEVI; LIDIA FATMAH ALAWIYAH (Society for Indonesian Biodiversity, 2020)
Abstract. Rindita, Anggia V, Rahmaesa E, Devi RK, Alawiyah LF. 2020. Exploration, phenolic content determination, and antioxidant activity of dominant pteridophytes in Gunung Malang Village, Mount Halimun Salak National Park, Indonesia. Biodiversitas 21: 3676-3682. Pteridophytes have been known to have pharmacological activities as an antioxidant, anti-inflammation, antimicrobials, and anticancer, such as Selaginella sp. In this research, exploration was conducted in Gunung Malang Village, Mount Halimun Salak National Park (TNGHS), West Java. Samples were collected by purposive sampling method, related to its abundant populations, Histiopteris incisa, Nephrolepis biserrata, and Selaginella willdenowii were collected based on different height and light intensity. Abiotic factors were measured to know their ecological requirements. Samples were extracted using ultrasonic method. Organoleptic test, yield, and phytochemical screening were done for the crudes extract. Total phenolic level was determined with Folin-Ciocalteu method and antioxidant activity test with DPPH. Phytochemical screening showed that H. incisa contains phenolics, saponins, tannins, and steroids; N. biserrata contains phenolics, flavonoids, and saponins while S. willdenowii contains phenolics, alkaloids, flavonoids, saponins, and tannins. Phenolic content of H. incisa and N. biserrata from 700 m. asl.was 9.8523 mg GAE/g ± 0.9694 and 17.5399 mg GAE/g ± 0.5350 respectively, from 1000 m. asl. was 18.1231 mgGAE/g ±2.1535 and 8.8468 mg GAE/g ± 0.1437. S. willdenowii extract collected from shaded canopy forest was 19.2324 mg GAE/g ± 0.6041 and opened canopy forest was 38.7087 mg GAE/g ± 1.484. Antioxidant IC50 of H. incisa and N. biserrata from 700 m. asl. respectively was 96.4271 ppm and 85.1907 ppm, while from 1000 m. asl. was 75.6381 ppm and 95.0678 ppm, S. willdenowii from the closed canopy is 101.7326 ppm, while from the opened canopy was 92.0998 ppm. This study shows that all ferns tested gave significant antioxidant activity and was influenced by environmental factors.